ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEPUASAN PENGUNJUNG PANTAI PANJANG KOTA BENGKULU - Markoni Markoni (Universitas Prof. Dr. Hazairin SH, 2020)
This study discusses the influence of natural beauty, facilities, transportation, and cleanliness to the visitors of Panjang BeachBengkulu City. The population was 96 respondents, using the Accidental Sampling technique. To analyze the data, the Multiple Regression, Partial Correlation and Simultaneous Correlation methods were used. Natural Beauty, Facilities, Transportation and Cleanliness both simultaneously and partially have a significant and direct effect on the Visitors Satisfaction of the Panjang Beach Bengkulu City, with the biggest contribution being the Transportation factor, followed by Cleanliness, Natural Beauty, and the lowest contribution is the Facilities variable. Thus the Beauty of Nature, Facilities, Transportation, and Cleanliness both simultaneously and significantly to the Satisfaction of Panjang Beach Bengkulu City, therefore the four factors that need to get the attention of the Bengkulu Provincial Government in taking policies and planning for the management of the Panjang Beach Bengkulu Cityand the Tourism sector others in Bengkulu Province.